Mewujudkan Lingkungan Belajar Aman Pada Satuan PAUD Perspektif “Seri 6 PAUD Berkualitas (KEMENDIKBUDRISTEK)” - Aina Yulifaatun Mufida; Hibana (Early Childhood Islamic Education, 2023)
The school environment is central to children's direct learning. In developing potential in early childhood at school, the environmental design must prioritize safety, comfort and fun. KEMENDIKBUDRISTEK has Quality ECD guidelines on safe learning environments for early childhood. The purpose of the study was to determine the indicators and how to realize a safe environment in PAUD units. The method in the study used a literature study, namely data sources obtained from books, articles, scientific publications related to a safe learning environment in PAUD. Indicators in a safe learning environment in PAUD units, namely building safety, environmental safety, availability of first aid facilities and unit policies on anti-violence. Safe buildings must meet sturdy and stable standards and environmental safety must pay attention to the safety of children when entering school, during learning and returning home. The availability of first aid facilities in PAUD units aims to anticipate and provide first aid to children who have an accident or illness at school. Anti-violence unit policy in PAUD through three efforts, namely awareness, prevention and handling efforts. Therefore, PAUD units must pay attention to indicators in realizing a safe environment for early childhood so that development is optimally stimulated.